Effect of gold-nanoparticle size on microfiber saturable absorber for mode-locked erbium-doped fiber lasers - Naharuddin, N.Z.A.; Abu Bakar, M.H.; Tamchek, N.; Alresheedi, M.T.; Abas, A.F.; Goh, C.S.; Zainuddin, N.H.; Mahdi, M.A. (Elsevier, 2023)
The optical performance of passively mode-locked erbium-doped fiber laser incorporating goldnanoparticles (Au-NPs) of different sizes as saturable absorbers (SAs) was compared. A composite of Au-NPs with polydimethylsiloxane was spin coated on the surface of a microfiber waveguide. The fabricated Au-NP-based SA was deployed in a ring cavity erbium-doped fiber laser and its lasing performance was evaluated by comparing SA characteristics as well as pulse qualities among the different Au-NP sizes. The optimum pulse performance was realized when the SA was fabricated with 20 and 40 nm Au-NP size. For the former, time-bandwidth product of 0.34 was demonstrated which was the closest to its bandwidth-limited pulse. As for the latter, the fabricated SA exhibited 4.0 modulation depth and an average pulse duration of 886.7 fs. The research work has demonstrated the functionality of Au-NPs as a saturable absorption material for ultrashort pulses generation. In addition, the influence of nanomaterial size towards the characteristics of saturable absorbers, ergo the quality of laser pulse, was verified. This finding is also valuable in customizing ultrashort pulse output that can effectively suit system performance need.